2020
DOI: 10.1021/acschembio.9b00975
|View full text |Cite
|
Sign up to set email alerts
|

Isoenzyme-Selective Inhibitors of Human Neuraminidases Reveal Distinct Effects on Cell Migration

Abstract: The human neuraminidase enzymes (NEU1, NEU2, NEU3, and NEU4) are a class of enzymes implicated in pathologies including cancer and diabetes. Several reports have linked neuraminidase activity to the regulation of cell migration in cancer cells. Using an in vitro cell migration assay on fibronectin (FN) coated surfaces, we have investigated the role of these enzymes in integrin-mediated cell migration. We observed that neuraminidase inhibition caused significant retardation of cell migration in breast cancer (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 80 publications
(195 reference statements)
1
23
1
Order By: Relevance
“…The precise mechanism has not yet been clarified. In fact, a recent contribution demonstrated that the inhibition of NEU3 activity caused significant retardation of cell migration in breast cancer and prostate cancer cell lines [26], and another study revealed that NEU3 forced overexpression acts on Crumbs3 in modulating cell migration of colon cancer cells [27]. However, if NEU3 acts directly or through EGFR, it needs more studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise mechanism has not yet been clarified. In fact, a recent contribution demonstrated that the inhibition of NEU3 activity caused significant retardation of cell migration in breast cancer and prostate cancer cell lines [26], and another study revealed that NEU3 forced overexpression acts on Crumbs3 in modulating cell migration of colon cancer cells [27]. However, if NEU3 acts directly or through EGFR, it needs more studies.…”
Section: Discussionmentioning
confidence: 99%
“…Zanamivir, an antiviral and bacterial NEU inhibitor, has low micromolar activity against NEU3 but also against NEU2. 2,3-dehydro-2-deoxy-N-acetylneuraminic acid (DANA) is a pan-selective inhibitor of all human NEU isoenzymes with a modest preference for NEU3 and NEU4 [26]. Moreover, it has been demonstrated that the modulation of sialidase expression might be effectively achieved by the appropriate use of recombinant sialidases for upregulation or specific inhibitors, antibodies and siRNAs for downregulation [42].…”
Section: Discussionmentioning
confidence: 99%
“…This effect of Neu1 is mediated through the Wnt/b-catenin pathway [63]. In a recent study on MDA-MB-231 (breast cancer) and PC-3 (prostate cancer) cells, Neu1 inhibition led to enhanced migration, while Neu2 and Neu3 inhibition led to a decrease in cell migration [64]. The expression of Neu2 is shown to be upregulated in prostate cancer [65], but interestingly it also induces apoptosis in the leukaemia cell line [66].…”
Section: Mechanism Of Hypersialylation In Cancer and Its Role In Cancer Progressionmentioning
confidence: 99%
“…1 Catabolism of sialic acids by the human neuraminidase (hNEU) enzymes regulates cellular processes including cell-cell interactions, host pathogen interactions, tumor malignancy, and cell migration. [2][3][4] To date, four hNEU isoenzymes have been identified (NEU1-NEU4). 2 Previous work has found that sialic acid presentation influences recognition by hNEU and that isoenzymes have distinct substrate specificities.…”
Section: Introductionmentioning
confidence: 99%